FORMULASI FAKTOR MODIFIKASI KUAT TARIK BELAH UNTUK KUAT GESER BETON TANPA AGREGAT KASAR - Christianto, Daniel; Pranoto, Wati Asriningsih; Jusuf, Andrew Hartanto; Kho, Dhea Angelica; Tavio (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
One way to create high strength concrete is to eliminate coarse aggregate from the concrete mixture. The lack of recommendations for the design of concrete without coarse aggregate can cause failures that must be avoided, especially brittle shear failures. One way to account for the properties of the concrete without coarse aggregate is to use a splitting tensile strength factor in the normalweight concrete shear strength equation. In this research, cylindrical specimens with the size of 150 mm × 300 mm and 100 mm × 200 mm were tested in compression according to ASTM C496 to obtain the concrete splitting tensile strength. All concrete specimens were made with a maximum aggregate size of 0,6 mm, superplasticizer, and silica fume. The specimens were treated through a curing process of 58 days before being tested. Based on the analysis of the test results, concrete without coarse aggregate with a compressive strength of 50.87 to 60.67 MPa has splitting tensile strength of 1.17 to 1.71 times the splitting tensile strength of normal concrete. The application of splitting tensile strength modification factor (λ) based on test results can gives a better prediction of the shear strength of concrete without coarse aggregate. Abstrak Salah satu cara untuk membuat beton mutu tinggi adalah dengan mengeliminasi agregat kasar dari campuran beton. Kurangnya rekomendasi desain beton tanpa agregat kasar dapat menyebabkan kegagalan yang harus dihindari, terutama kegagalan geser yang bersifat getas. Salah satu cara memperhitungkan sifat beton tanpa agregat kasar adalah dengan menggunakan faktor kuat tarik belah pada persamaan kuat geser beton normal. Dalam penelitian ini, benda uji silinder berukuran 150 mm × 300 mm dan 100 mm × 200 mm diuji tekan sesuai ASTM C496 untuk mendapatkan kuat tarik belah beton. Semua spesimen beton dibuat dengan ukuran agregat maksimum sebesar 0,6 mm, superplasticizer, dan silica fume, serta dirawat melalui proses curing selama 58 hari sebelum diuji tekan dan tarik belah. Berdasarkan analisis hasil pengujian, beton tanpa agregat kasar dengan kuat tekan sebesar 50,87 hingga sampai 60,67 MPa memiliki kuat tarik belah sebesar 1,17 sampai 1,71 kali kuat tarik belah beton normal. Penerapan faktor modifikasi kuat tarik belah (λ) berdasarkan hasil pengujian dapat memberikan prediksi kekuatan geser beton tanpa agregat kasar yang lebih baik.